Resin composition, adhesive film and printed circuit board containing the same
By using core-shell copolymer toughener and gradient polymer in the adhesive film, the problem of elongation reduction caused by high-filled inorganic fillers is solved, and the high-temperature elongation and copper foil peel strength is improved, while maintaining low CTE performance. Suitable for thin-line applications of printed circuit boards.
Patent Information
- Application Number
- CN202211622409.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-16
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-12-16
AI Technical Summary
Existing films without reinforcement materials are negatively affected after the introduction of high-filled inorganic fillers, and the increased toughener will deteriorate other properties, especially CTE, making it difficult to simultaneously improve the elongation of high temperature and copper foil peel strength while maintaining Low CTE.
A core-shell copolymer toughening agent is used to prepare a gradient polymer by emulsion polymerization, and combined with appropriate resin and filler ratios, a resin composition with high high temperature elongation and copper foil peel strength is formed to reduce CTE.
It effectively improves the high-temperature elongation of the adhesive film and the peel strength of the copper foil, while maintaining low CTE performance. It is suitable for printed circuit boards with multi-layer laminated plates, especially multi-layer laminated plates with thin lines.
Smart Images

Figure BDA0004002610510000111 
Figure BDA0004002610510000112
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of resin adhesive films and relates to a resin composition and an adhesive film and a printed circuit board containing the same. Background Art
[0002] As electronic information products are mainly oriented towards the design trend of being light, thin, short and multifunctional in the future, the printed circuit substrate, as the main support for electronic components, is also constantly improving its technical level to provide high-density wiring, thin shape, fine aperture, multi-dimensional, etc. The substrate material determines the performance of the printed circuit substrate to a large extent, so it is urgent to develop a new generation of base materials.
[0003] Adhesive films or resin-coated copper foils without reinforcement materials are being developed and applied as a new generation of matrix materials because they can achieve thinner shapes, high-density wiring, fine pores, and multi-dimensional three-dimensional molding. Since there is no reinforcement material, high-filled inorganic fillers are generally added to improve the thermal expansion coefficient, chemical resistance, mechanical strength and processing performance of the adhesive film material. However, it is precisely because of the introduction of high-filled inorganic fillers that the elongation of the adhesive film is negatively affected. In order to compensate for the elongation, toughening agents such as rubber are usually added for toughening. However, the newly introduced toughening agents will deteriorate other properties. How to improve the elongation of the adhesive film without reducing other properties, especially CTE, is the focus of research.
[0004] Therefore, in the art, it is desired to develop a material for fine circuits that can improve the elongation of the adhesive film after high temperature and the peel strength of the copper foil, while maintaining a low CTE performance. Summary of the invention
[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a resin composition, and an adhesive film and a printed circuit board containing the same.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In one aspect, the present invention provides a resin composition, comprising the following components in parts by weight:
[0008] Resin 30-70 parts
[0009] Filler 30-60 parts
[0010] 1-10 parts of core-shell copolymer toughening agent,
[0011] The core-shell copolymer comprises a polymer core and at least two polymer shells, each of the at least two polymer shells comprises a different polymer, and at least one shell comprises a gradient polymer.
[0012] In the present invention, the core-shell copolymer toughening agent is selected so that the adhesive film and the resin-coated copper foil prepared from the resin composition have high high-temperature elongation and copper foil peel strength, and have a lower CTE, which can well solve the problem of negative elongation caused by the addition of high-filled inorganic fillers, and can be applied to printed circuit boards of multi-layer laminated boards, especially printed circuit boards of multi-layer laminated boards with fine circuits.
[0013] The gradient polymer is a copolymer, which is composed of at least two different monomers (A) and monomers (B) and has a gradient in the repeating units arranged from most of the monomers (A) to most of the monomers (B) along the copolymer. Such core-shell copolymers can be prepared by emulsion polymerization, for example, a suitable method is a two-stage polymerization technique, wherein a core and a shell are produced in two sequential emulsion polymerization stages. If there are more shells, then another emulsion polymerization stage occurs. In the polymerization stage reaction, the first monomer of styrene is mainly mixed during the initial stage of polymerization, while increasing the amount of the second monomer of methyl methacrylate, until methyl methacrylate is mainly or completely mixed during the polymerization in the final stage, thereby forming a gradient zone. For details, see CN102603989A and CN102585101A patents to obtain more detailed information about the method for manufacturing such core-shell copolymers. Such core-shell copolymers are also commercially available, for example, Arkema describes CLEARSTRENGTH XT100 and Dow Chemical describes PARALOID EXL-2650J as methyl methacrylate-butadiene-styrene core-shell copolymer toughening agents, which have good compatibility and dispersibility in the resin composition.
[0014] Preferably, the core of the core-shell copolymer toughener comprises polybutadiene, the middle shell comprises a gradient polymer of styrene, and the outer shell comprises methyl methacrylate.
[0015] In the present invention, the content of the resin in the resin composition is 30 parts, 35 parts, 40 parts, 45 parts, 48 parts, 50 parts, 55 parts, 58 parts, 60 parts, 65 parts, 68 parts or 70 parts.
[0016] In the present invention, the content of filler in the resin composition is 30 parts, 35 parts, 38 parts, 40 parts, 45 parts, 48 parts, 50 parts, 55 parts, 58 parts or 60 parts.
[0017] In the present invention, the content of the core-shell copolymer toughening agent is 1 part, 2 parts, 3 parts, 5 parts, 7 parts, 9 parts or 10 parts.
[0018] In the present invention, the "parts" and "parts by weight" involved are all calculated based on solid content and do not include solvents, dispersants, etc.
[0019] Preferably, the resin is any one of epoxy resin, phenolic resin, cyanate ester, polyphenylene ether, maleimide resin, hydrocarbon resin, acrylate resin, polyimide resin, silicone resin, polyester resin or polystyrene, or a combination of at least two thereof.
[0020] Preferably, the epoxy resin includes any one or a combination of at least two of bisphenol A epoxy resin, bisphenol F epoxy resin, phosphorus-containing epoxy resin, MDI-modified epoxy resin, novolac epoxy resin, biphenyl epoxy resin, dicyclopentadiene epoxy resin, naphthalene-containing epoxy resin or alicyclic epoxy resin.
[0021] Preferably, the filler is an inorganic filler.
[0022] Preferably, the filler is a silica filler, preferably spherical silica.
[0023] Preferably, the resin composition further comprises a curing agent, and the curing agent comprises any one of phenolic resin and active ester or a combination of both.
[0024] Preferably, the phenolic resin includes any one of bisphenol A phenolic resin, phenolic resin, biphenyl phenolic resin, dicyclopentadiene phenolic resin or naphthyl phenolic resin or a combination of at least two thereof.
[0025] In the present invention, when the main resin contains epoxy resin, its curing agent may be phenolic resin, active ester or cyanate ester. Thiol or amine (such as dicyandiamide or aromatic amine) curing agents are not suitable for use because they will lead to the problem of increased CTE of the film.
[0026] Preferably, the content of the curing agent in the resin composition is 10-30 parts, for example, 10 parts, 15 parts, 18 parts, 20 parts, 25 parts, 28 parts or 30 parts.
[0027] In the present invention, a thermoplastic resin may be further added without affecting the comprehensive performance of the resin composition. Examples of the thermoplastic resin include polyvinyl acetal resin, polyamide-imide resin, polyether sulfone resin, polysulfone resin and the like.
[0028] On the other hand, the present invention provides a resin glue solution, which is obtained by dissolving or dispersing the above-mentioned resin composition in a solvent.
[0029] As the solvent in the present invention, there is no particular limitation. As specific examples, alcohols such as methanol, ethanol, and butanol, ethers such as ethyl cellosolve, butyl cellosolve, ethylene glycol-methyl ether, carbitol, and butyl carbitol, ketones such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, aromatic hydrocarbons such as toluene, xylene, and mesitylene, esters such as ethoxyethyl acetate and ethyl acetate, nitrogen-containing solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone can be cited. The above solvents can be used alone or in combination of two or more. Preferably, aromatic hydrocarbon solvents such as toluene, xylene, and mesitylene are mixed with ketone fluxes such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. The amount of the solvent used can be selected by those skilled in the art according to their own experience so that the obtained resin glue reaches a viscosity suitable for use.
[0030] On the other hand, the present invention provides an adhesive film, which includes a release film, the resin composition as described above attached to the release film after coating and drying, and a protective film covering the resin composition.
[0031] The adhesive film of the present invention, because it contains the resin composition as described above, can have higher high-temperature elongation and copper foil peeling strength, and lower CTE.
[0032] Preferably, the thickness of the adhesive film is 5-300 μm, for example 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, 100 μm, 150 μm, 180 μm, 200 μm, 230 μm, 250 μm, 280 μm or 300 μm, preferably 10-200 μm, further preferably 20-100 μm.
[0033] Preferably, the elongation of the adhesive film at 150° C. after curing is 10-20%, for example, 10%, 12%, 15%, 18% or 20%.
[0034] Preferably, after the adhesive film is cured, the peel strength of the electroplated copper foil is greater than 6.0 N / cm, for example, 6.2 N / cm, 6.5 N / cm, 6.8 N / cm, 7.0 N / cm, 7.2 N / cm, 7.5 N / cm, 7.8 N / cm or 8.0 N / cm.
[0035] On the other hand, the present invention provides a resin-coated copper foil, comprising a copper foil, a resin layer and a protective film coated on the resin layer, wherein the resin layer is the above-mentioned resin composition attached to the copper foil after coating and drying.
[0036] Preferably, the thickness of the resin layer is 5-300 μm, for example 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, 100 μm, 150 μm, 180 μm, 200 μm, 230 μm, 250 μm, 280 μm or 300 μm, preferably 10-200 μm, further preferably 20-100 μm.
[0037] Preferably, the copper foil has a thickness of 1-105 μm, for example, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, 100 μm or 105 μm, preferably 3-35 μm, further preferably 5-18 μm.
[0038] In another aspect, the present invention provides a prepreg, comprising a substrate and the above-mentioned resin composition attached to the substrate by impregnation and drying.
[0039] The semi-cured sheet of the present invention may also be referred to as a prepreg or a bonding sheet, and the substrate of the present invention may also be referred to as a reinforcing material.
[0040] Preferably, the substrate is E-glass fiber cloth, NE-glass fiber cloth, quartz glass fiber cloth or aromatic amine cloth.
[0041] In another aspect, the present invention provides a laminate comprising at least one prepreg as described above.
[0042] In another aspect, the present invention provides a metal foil-clad laminate, comprising one or at least two laminated prepregs as described above, and metal foil located on one side or both sides of the laminated prepregs.
[0043] Preferably, the metal foil is copper foil.
[0044] In another aspect, the present invention provides a printed circuit board, comprising one or at least two laminated prepregs as described above.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] In the present invention, the core-shell copolymer toughening agent is selected so that the adhesive film and the resin-coated copper foil prepared from the resin composition have high high-temperature elongation and copper foil peel strength, and have a lower CTE, which can well solve the problem of negative elongation caused by the addition of high-filled inorganic fillers, and can be applied to printed circuit boards of multi-layer laminated boards, especially printed circuit boards of multi-layer laminated boards with fine circuits. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0048] Example 1
[0049] 40 parts of epoxy resin (HEXION, EPR627) and 19 parts of phenolic resin (Dow Chemical, XZ92741), 40 parts of silica (admatechs, 2050MB), and 1 part of core-shell copolymer toughener (ARKEMA, XT100) were added to butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.
[0050] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.
[0051] Example 2
[0052] 37 parts of epoxy resin (Nippon Kayaku, NC3000H) and 18 parts of phenolic resin (HEXION, PHL6635), 40 parts of silica (admatechs, 2050MB), and 5 parts of core-shell copolymer toughening agent (ARKEMA, XT100) were added to butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.
[0053] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.
[0054] Example 3
[0055] 34 parts of epoxy resin (Momentive, EPIKOTE1001) and 16 parts of active ester (Japan DIC, HPC-8000-65T), 40 parts of silica (admatechs, 2050MB), and 10 parts of core-shell copolymer toughening agent (ARKEMA, XT100) were added to butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.
[0056] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.
[0057] Example 4
[0058] 25 parts of cyanate ester (Lonza, BA3000) and 30 parts of maleimide resin (CYTEC, M5250), 40 parts of silica (admatechs, 2050MB), 5 parts of core-shell copolymer toughener (ARKEMA, XT100) were added to butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.
[0059] The above solution was coated on the release film, dried, and then baked in a 120℃ oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100℃, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.
[0060] Example 5
[0061] 30 parts of polyphenylene ether (SABIC, MX90), 25 parts of hydrocarbon resin (Japan Soda, B3000), 40 parts of silica (admatechs, 2050MB), and 5 parts of core-shell copolymer toughener (Dow Chemical, EXL-2650J) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.
[0062] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.
[0063] Example 6
[0064] The only difference from Example 2 is that the phenolic resin (HEXION, PHL6635) in Example 2 is replaced by an amine curing agent (BASF, dicyandiamide) in equal parts by weight.
[0065] Comparative Example 1
[0066] 40 parts of epoxy resin (HEXION, EPR627), 20 parts of phenolic resin (Dow Chemical, XZ92741) and 40 parts of silica (admatechs, 2050MB) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.
[0067] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.
[0068] Comparative Example 2
[0069] 39.5 parts of epoxy resin (HEXION, EPR627) and 20 parts of phenolic resin (Dow Chemical, XZ92741), 40 parts of silica (admatechs, 2050MB), and 0.5 parts of core-shell copolymer toughener (ARKEMA, XT100) were added to a butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.
[0070] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.
[0071] Comparative Example 3
[0072] 33 parts of epoxy resin (Momentive, EPIKOTE1001) and 15 parts of phenolic resin (Japan Meiwa, 7851H), 40 parts of silica (admatechs, 2050MB), and 12 parts of core-shell copolymer toughening agent (ARKEMA, XT100) were added to butanone solvent and stirred for 2 hours to form a solution with a solid content of 65%.
[0073] The above solution was coated on the release film, dried, and then placed in a 120°C oven for 5 minutes to obtain a semi-cured resin layer film. The semi-cured film (thickness 40μm) and the browned PCB board were pressed and cured (temperature 100°C, pressure 0.5MPa, time 1min), the release film was torn off, and the surface was treated and copper electroplated to form a laminated printed circuit board with circuits.
[0074] Comparative Example 4
[0075] The only difference from Example 2 is that the core-shell copolymer toughening agent (ARKEMA, XT100) in Example 2 is replaced by an equal weight portion of nitrile rubber (ZEON, Nipol 1072CG).
[0076] Comparative Example 5
[0077] The only difference from Example 2 is that the core-shell copolymer toughening agent (ARKEMA, XT100) in Example 2 is replaced by an equal weight portion of toughening agent AC-3816 (Aike Co., Ltd.).
[0078] Comparative Example 6
[0079] The only difference from Example 2 is that the core-shell copolymer toughening agent (ARKEMA, XT100) in Example 2 is replaced by an equal weight portion of toughening agent M732 (Kanehae Chemical).
[0080] The performance tests of the embodiments and comparative examples were carried out as follows:
[0081] (1) Elongation: DMA method, constant temperature 150 ° C for 5 min, preload 0.01 N, 3 N / min increased to 17.5 N / min;
[0082] (2) Copper foil peel strength: The IPC-TM-650 2.4.9 method is used to test the peel strength of the copper foil layer of the surface copper electroplating;
[0083] (3) Fine line capability: The percentage of short circuits in the test circuit after reflow soldering. When the percentage is greater than 90%, it is "excellent", when the percentage is less than 80%, it is "poor", and the rest is "good";
[0084] (4) CTE: tested using IPC-TM-650 2.4.24.5 method;
[0085] (5) Tg (DSC): tested using IPC-TM-650 2.4.25 method.
[0086] The performance tests of the above embodiments and comparative examples are compared in Tables 1 and 2 below.
[0087] Table 1
[0088]
[0089] Table 2
[0090]
[0091] From Table 1 and Table 2, it can be seen that the film elongation and copper foil peeling strength of Examples 1-5 are high, the CTE is low, and the reliability of thin circuits is excellent. Example 6 uses an amine curing agent to cure epoxy, and the CTE of the film is significantly increased, which is difficult to meet the performance requirements.
[0092] Comparative Example 1 did not add the core-shell copolymer toughening agent described in the present invention, and the elongation of the film was low, and the copper foil peeling strength was low; the amount of core-shell copolymer toughening agent added in Comparative Example 2 was too small, the elongation was not improved, and the copper foil peeling strength was low; Comparative Example 3 added too much core-shell copolymer toughening agent, resulting in an increase in the CTE of the film and deterioration in performance. Comparative Example 4 introduced nitrile rubber as a toughening agent, resulting in an increase in the CTE of the film, a decrease in Tg, and deterioration in performance. Comparative Examples 5 and 6, other core-shell toughening agents were added, and their toughening effect was not as good as the core-shell copolymer toughening agent of the present application, and the CTE performance of the film was relatively poor.
[0093] The applicant declares that the present invention uses the above embodiments to illustrate the resin composition of the present invention and the adhesive film and printed circuit board containing the same, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A resin composition, characterized in that The resin composition comprises the following components in parts by weight: Resin 35-70 parts Filler 40-60 parts 1-10 parts of core-shell copolymer toughening agent; The core-shell copolymer toughener comprises a core of polybutadiene, a middle shell of a gradient polymer of styrene, and an outer shell of methyl methacrylate; The resin is any one of epoxy resin, cyanate ester, polyphenylene ether, maleimide resin or hydrocarbon resin, or a combination of at least two of them.
2. The resin composition according to claim 1, characterized in that The epoxy resin includes any one or a combination of at least two of bisphenol A epoxy resin, bisphenol F epoxy resin, phosphorus-containing epoxy resin, MDI-modified epoxy resin, novolac epoxy resin, biphenyl epoxy resin, dicyclopentadiene epoxy resin, naphthalene-containing epoxy resin or alicyclic epoxy resin.
3. The resin composition according to claim 1, characterized in that The filler is an inorganic filler.
4. The resin composition according to claim 1, characterized in that The filler is a silicon dioxide filler.
5. The resin composition according to claim 4, characterized in that The silicon dioxide filler is spherical silicon dioxide.
6. The resin composition according to claim 1, characterized in that The resin composition further comprises a curing agent, and the curing agent comprises any one of phenolic resin and active ester or a combination of both.
7. The resin composition according to claim 6, characterized in that The phenolic resin includes any one of bisphenol A phenolic resin, phenolic resin, biphenyl phenolic resin, dicyclopentadiene phenolic resin or naphthyl phenolic resin or a combination of at least two thereof.
8. The resin composition according to claim 6, characterized in that The content of the curing agent in the resin composition is 10-30 parts.
9. A resin glue, characterized in that: The resin composition is obtained by dissolving or dispersing the resin composition as claimed in any one of claims 1 to 8 in a solvent.
10. An adhesive film, characterized in that: The adhesive film comprises a release film, a resin composition according to any one of claims 1 to 8 attached to the release film after coating and drying, and a protective film covering the resin composition.
11. The adhesive film according to claim 10, characterized in that: The thickness of the adhesive film is 5-300 μm.
12. The adhesive film according to claim 11, characterized in that: The thickness of the adhesive film is 10-200 μm.
13. The adhesive film according to claim 12, characterized in that: The thickness of the adhesive film is 20-100 μm.
14. The adhesive film according to claim 10, characterized in that: After the adhesive film is cured, the elongation at 150° C. is 10-20%.
15. The adhesive film according to claim 10, characterized in that: After the adhesive film is cured, the peel strength of the electroplated copper foil is greater than 6.0 N / cm.
16. A resin-coated copper foil, characterized in that: The resin-coated copper foil comprises a copper foil, a resin layer and a protective film coated on the resin layer. The resin layer is a resin composition as claimed in any one of claims 1 to 8 attached to the copper foil after coating and drying.
17. The resin-coated copper foil according to claim 16, wherein: The thickness of the resin layer is 5-300 μm.
18. The resin-coated copper foil according to claim 17, characterized in that The thickness of the resin layer is 10-200 μm.
19. The resin-coated copper foil according to claim 18, characterized in that: The thickness of the resin layer is 20-100 μm.
20. The resin-coated copper foil according to claim 16, wherein: The copper foil has a thickness of 1-105 μm.
21. A prepreg, characterized in that: The prepreg comprises a substrate and the resin composition according to any one of claims 1 to 8 attached to the substrate after impregnation and drying.
22. A laminated board, characterized in that: The laminate comprises at least one prepreg according to claim 21.
23. A metal foil-clad laminate, characterized in that: The metal foil clad laminate comprises one or at least two stacked prepregs as claimed in claim 21, and metal foil located on one side or both sides of the stacked prepregs.
24. A printed circuit board, characterized in that: The printed circuit board comprises one or at least two superimposed prepregs according to claim 21.
Citation Information
Patent Citations
New core shell particle multistage polymer powder, its manufacturing process and composition comprising it
CN102585101A
Process for core shell impact modifiers and impact modified thermoplastic composition with enhanced hydrolytic resistance
CN102603989A
Thermosetting resin composition and copper foil-clad laminated sheet prepared by using thermosetting resin composition
CN102850727A